2005
DOI: 10.1359/jbmr.050406
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Fractures in the Mouse Mutant sfx Are Caused by Deletion of the Gulonolactone Oxidase Gene, Causing Vitamin C Deficiency

Abstract: Using a mouse mutant that fractures spontaneously and dies at a very young age, we identified that a deletion of the GULO gene, which is involved in the synthesis of vitamin C, is the cause of impaired osteoblast differentiation, reduced bone formation, and development of spontaneous fractures.Introduction: A major public health problem worldwide, osteoporosis is a disease characterized by inadequate bone mass necessary for mechanical support, resulting in bone fracture. To identify the genetic basis for osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 50 publications
4
68
0
Order By: Relevance
“…Our data provide a plausible explanation of these findings: decreased levels of ascorbic acid would elevate bone turnover causing increases in both osteoclastic and osteoblastic function, but with a net bone loss. Indeed, sfx mice deficient in an enzyme essential for the production of ascorbic acid undergo spontaneous fractures at an early age (32). Thus, we speculate that the treatment of postmenopausal osteoporosis might benefit from supplementation with ascorbic acid.…”
Section: Discussionmentioning
confidence: 91%
“…Our data provide a plausible explanation of these findings: decreased levels of ascorbic acid would elevate bone turnover causing increases in both osteoclastic and osteoblastic function, but with a net bone loss. Indeed, sfx mice deficient in an enzyme essential for the production of ascorbic acid undergo spontaneous fractures at an early age (32). Thus, we speculate that the treatment of postmenopausal osteoporosis might benefit from supplementation with ascorbic acid.…”
Section: Discussionmentioning
confidence: 91%
“…This article must therefore be hereby marked "advertisement" in accordance with 18vincing evidence that AA also influences differentiation of other cell type lineages, such as neuronal cells, that produce little or no matrix (16). Furthermore, the gulonolactone oxidase knock-out mice have normal levels of proline hydroxylation and collagen production in the tail, mammary gland, and tumors, whereas these mice show widespread abnormalities in multiple organs besides the bone (2,17). In addition, it has been demonstrated that AA can stimulate the expression of a number of osteogenic marker genes in the presence of collagen synthesis inhibitors and can induce chondrocyte hypertrophy independent of production of a collagen-rich matrix (18).…”
mentioning
confidence: 88%
“…In addition, several epidemiological studies have shown that a lower level of blood AA, also known as vitamin C, may substantially increase the risk of hip fracture in smokers and elderly patients, whereas supplementation of antioxidant vitamins greatly reduces the frequency of osteoporotic fractures (6 -8). These genetic studies together with clinical observations have reinforced the critical role of antioxidant vitamins in maintaining bone health (2). Although it is well known that AA is required for osteoblast differentiation, the molecular mechanisms by which AA regulates bone formation and mineralization remain to be elucidated.…”
mentioning
confidence: 99%
See 2 more Smart Citations